Post-translational histone modifications associated with the development of metabolic dysfunction-associated fatty liver disease. Part 2. Histone methylation - O.E. Abaturov; A.O. Nikulina (Gastroenterologìa)
Based on the analysis of literary sources of databases Pubmed, MEDLINE, The Cochrane Library, Embase, the authors highlight the essential role of epigenetic modulations in the pathogenesis of metabolic dysfunction-associated fatty liver disease. They give general provisions regarding post-translational histone modifications, which are associated with the development of metabolic dysfunction-associated fatty liver disease, namely, the features of their methylation, post-translational modifications of methylation of lysine residues (sites H3K4, H3K27, H3K36, H3K79, H4K20, H3K23, H3K63 and H4K12), arginine residues (sites H2AR3, H4R3, H3R2, H3R8 and H3R26). Histone methylation and demethylation, mediating the expression of key genes involved in carbohydrate and lipid metabolism, determine both the occurrence and development of steatosis, inflammation and fibrosis of the liver in patients with metabolic dysfunction-associated fatty liver disease. Methylated markers H3K9, H3K27, H4K20 of histones are associated with packed heterochromatin and repression of gene transcription, while methylated markers H3K4, H3K36, H3K79 of histones are associated with activation of gene transcription. Methylation of lysine or arginine residues of histones is carried out by methyltransferases that use S-adenosylmethionine as a donor molecule. The methylated site of an arginine residue can be represented by a monomethylated, asymmetrically demethylated, or symmetrically demethylated marker, whereas demethylation of a lysine marker is mediated by demethylases. The authors provide data that in metabolic dysfunction-associated fatty liver disease, the main sites in which aberrant methylation is observed are H3K4, H3K9, H3K27, H4R3, H3R8, and H2AR3. Several genes of histone methyltransferases and histone demethylases have been identified, which are differentially expressed in patients with metabolic dysfunction-associated fatty liver disease and healthy people. The authors emphasize that the enzymes involved in the histone methylation and demethylation are targets of future drugs, which will certainly improve the effectiveness of drug therapy in patients with metabolic dysfunction-associated fatty liver disease.